Temporal relationship between Women’s empowerment and utilization of antenatal care services: lessons from four National Surveys in sub-Saharan Africa - Kareem, Yusuf O.; Morhason-Bello, Imran O.; OlaOlorun, Funmilola M.; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background In November 2016, the WHO four-visit focused antenatal care (FANC) model adopted in sub-Saharan Africa (SSA) was reverted to eight contacts or more as a response to reducing the global perinatal and maternal deaths and in achieving the sustainable development goal (SDG) 3. Women’s empowerment, which connote the social standing, position and the ability of women to make life decisions and choices has been associated with the maternal health seeking behaviour and outcomes. This study examined the association between women’s empowerment and the WHO ANC model of eight visits or more, and early first antenatal visit among pregnant women. In addition, we explored the association between women’s empowerment and the WHO FANC model to allow for comparison for countries that have not adopted the recent WHO ANC model. Methods The most recent (2018) Demographic and Health Survey (DHS) datasets conducted in SSA were used for analyses. We used all available indicators of women’s empowerment captured in the DHS. The 30 variables on women’s empowerment were classified into eight components using exploratory factor analysis. We fitted separate ordinal logistic regression to assess association between antenatal care utilization (number of visits and time of first antenatal visit) and women empowerment factors while adjusting for other covariates. Analysis was performed with STATA 15.0 and adjusted for complex survey design, p-value< 0.05 were used for interpretation of results. Results The proportion of women who attended eight or more ANC visits were 1.4, 2.7 and 3.5% in Zambia, Guinea and Mali, respectively. Zambia had the lowest prevalence of 8 or more ANC visits also had the highest prevalence of at least 4 visits (63.8%) and early first ANC visit (38.2%), while Nigeria with the highest prevalence of women with at least 8 visits (17.7%) had the lowest prevalence (17.6%) of women that attended ANC visit in their first trimester. Women’s empowerment was associated with more ANC visits and attending first ANC visit in the first trimester. However, these association with the women empowerment components varied significantly across the four SSA countries. Conclusion This study highlights the significant impact of women’s empowerment as a key factor for improving maternal health outcomes in SSA. It is imperative that government and development partners invest more on empowerment of women as part of strategic intervention to improve maternal health outcomes.